Prevalence of Diabetes and Associated Risk Factors among a Group of Prisoners in the Yaoundé Central Prison - Sylvain Raoul Simeni Njonnou; Jérôme Boombhi; Martine Claude Etoa Etoga; Aimée Tiodoung Timnou; Ahmadou Musa Jingi; Kevin Nkem Efon; Esther Astrid Mbono Samba Eloumba; Marie-Josiane Ntsama Essomba; Odette Kengni Kebiwo; Alice Ninon Tsitsol Meke; Stéphane Talbit Ndjonya; Mesmin Dehayem Yefou; et al. (Journal of Diabetes Research)
Background. Diabetes is a public health problem worldwide, associated with increased morbidity and mortality. According to the International Diabetes Federation (IDF) 2017 data, around 425 million people worldwide suffer from diabetes. This number is expected to increase to 629 million in 2045. Various occidental studies reported the increased prevalence and lower control of diabetes among prisoners. However, there is no data on the characteristics of inmates with diabetes in sub-Saharan Africa. Methods. A cross-sectional study among incarcerated detainees from the Yaoundé Central Prison was conducted from January to July 2017. Diabetes was defined according to the American Diabetes Association (ADA) criteria. Analyzed variables included phenotypic characteristics, lifestyle, the reason for detention, the sentence severity, and the length of detention. Results. We recruited 437 inmates (344 men) with an average age of 37.0 (95% CI: 35.9-38.3) years. The most frequent age group was 20 to 39 years with 281 (64.7%) inmates, and the mean prison stay was 29.1 (95% CI: 25.7-32.8) months. The prevalence of diabetes in the Yaoundé Central Prison was 9.4%. The main cardiovascular risk factors were a sedentary lifestyle (91.1%), hypertension (39.6%), smoking (31.6%), and alcohol consumption (28.1%). Hypertension (p=0.005), obesity (p=0.0006), smoking (p=0.04), sedentary lifestyle (p=0.04), major crime (p=0.007), and minor crime (p=0.003) were associated with diabetes in univariate analysis. In multivariate analysis, only obesity and sedentary lifestyle were associated with diabetes. Conclusion. Diabetes prevalence in the Yaoundé Central Prison was high, at 9.4%, compared to that in the general population. It was associated with other classical cardiovascular risk factors and factors linked to the sentence (minor and major crimes). This trial is registered with CE00617/CRERSHC/2016.